Confección de camisetas con logotipos con valores y su contribución al desarrollo social de los estudiantes de bachillerato de la Unidad Educativa Replica “Eugenio Espejo” cantón Babahoyo, provincia los Ríos - Garzon Mazacon, Verónica Margoth (2017)
The present investigative work had as purpose to carry out an analysis of all the related to the making of T-shirt logotipiadas with securities, with the purpose of fomenting the social development in the student and in turn to rescue ethical securities that there are you that one has come losing with spending of the days for lack of interest, the making of T-shirt with logotipiadas interests this students, with the purpose of being able to undertake its own business, because it consisted this way with economic resources that it facilitated them its conditions of life and in turn to be able to have its own micro company, this project interests them because it will serve them as help because they had the idea of putting its own business, they realized that they hardly applied the securities at much less home in its school, they decided to apply beginning to keep in mind the securities that you/they have left losing, this favored the relationships a lot between students and teacher them mejorora its quality of life and to generate sustainable and sustainable working sources and to be useful to the society